Spatial and temporal tracking of multi-layered cells sheet using reporter gene imaging with human sodium iodide symporter: a preclinical study using a rat model of myocardial infarction - Otani, Kentaro; Zeniya, Tsutomu; Kawashima, Hidekazu; Moriguchi, Tetsuaki; Nakano, Atsushi; Han, Chunlei; Murata, Shunsuke; Nishimura, Kunihiro; Koshino, Kazuhiro; Yamahara, Kenichi; Inubushi, Masayuki; Iida, Hidehiro (SPRINGER, 2025)
Purpose
This study aimed to evaluate a novel technique for cell tracking by visualising the activity of the human sodium/iodide symporter (hNIS) after transplantation of hNIS-expressing multilayered cell sheets in a rat model of chronic myocardial infarction.
Methods
Triple-layered cell sheets were generated from mouse embryonic fibroblasts (MEFs) derived from mice overexpressing hNIS (hNIS-Tg). Myocardial infarction was induced by permanent ligation of the left anterior descending coronary artery in F344 athymic rats, and a triple-layered MEFs sheets were transplanted to the infarcted area two weeks after surgery. To validate the temporal tracking and kinetic analysis of the transplanted MEFs sheets, sequential cardiac single-photon emission computed tomography (SPECT) examinations with a 99mTcO4- injection were performed. The cell sheets generated using MEFs of wild-type mice (WT) served as controls.
Results
A significantly higher amount of 99mTcO4- was taken into the hNIS-Tg MEFs than into WT MEFs (146.1 +/- 30.9-fold). The obvious accumulation of 99mTcO4- was observed in agreement with the region where hNIS-Tg MEFs were transplanted, and these radioactivities peaked 40-60 min after 99mTcO4- administration. The volume of distribution of the hNIS-Tg MEF sheets declined gradually after transplantation, implying cellular malfunction and a loss in the number of transplanted cells.
Conclusion
The reporter gene imaging with hNIS enables the serial tracking and quantitative kinetic analysis of cell sheets transplanted to infarcted hearts.